2016
DOI: 10.1007/s10959-016-0720-6
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Behavior of Semistable Lévy Exponents and Applications to Fractal Path Properties

Abstract: This paper proves sharp bounds on the tails of the Lévy exponent of an operator semistable law on R d . These bounds are then applied to explicitly compute the Hausdorff and packing dimensions of the range, graph, and other random sets describing the sample paths of the corresponding operator semi-selfsimilar Lévy processes. The proofs are elementary, using only the properties of the Lévy exponent, and certain index formulae.E n , and ε u denotes the Dirac measure at the point u ∈ R d . Operator semistable dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Theorem 1 is more general than [28,Theorem 1], where B is assumed to be a diagonal matrix with entries on the diagonal α j ∈ (1, 2) (1 ≤ j ≤ d). Note also that the dimension formula for double points in R 2 and R 3 is given in [14,Corollary 3.8]. Since M 3 = ∅ a.s. for d = 3 and M 2 = ∅ a.s. for d ≥ 4 (see the beginning of Section 4 for the proof), Theorem 1 completes the solution of the Hausdorff dimension problem for M k in the setting of symmetric operator semistable Lévy processes.…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Theorem 1 is more general than [28,Theorem 1], where B is assumed to be a diagonal matrix with entries on the diagonal α j ∈ (1, 2) (1 ≤ j ≤ d). Note also that the dimension formula for double points in R 2 and R 3 is given in [14,Corollary 3.8]. Since M 3 = ∅ a.s. for d = 3 and M 2 = ∅ a.s. for d ≥ 4 (see the beginning of Section 4 for the proof), Theorem 1 completes the solution of the Hausdorff dimension problem for M k in the setting of symmetric operator semistable Lévy processes.…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%
“…almost surely, where ξ = (ξ 1 , ..., ξ k ) for ξ j ∈ R d and · denotes the usual Euclidean norm in R d . Here we use the convention inf ∅ = d. Furthermore, in the case when X is a symmetric operator semistable Lévy process, [14,Corollary 2.2] gives the following estimate for its characteristic exponent Ψ: for every ε > 0, there exists a constant τ > 1 such that for all ξ ∈ R d with ξ ≥ τ , we have…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…, m p , then recently Wedrich [47] (cf. also [27]) has shown that for any operator semistable Lévy process X almost surely…”
Section: 2mentioning
confidence: 99%
“…Lastly, we will also derive exact Hausdorff measure functions for type B which turned out to be more challenging than asserted in Remark 1 of [8]. The Hausdorff dimension for the range and the graph of operator semistable Lévy processes have recently been determined in [11] and [23], respectively; see also [10] for an alternative derivation based on an index formula presented in [14]. The special case of the limit process in subsequent cointossing games of the famous St. Petersburg paradox has been studied in [12] in detail.The methods applied in this paper are similar to the ones used in [22] and [8] with complementary work necessary to handle the weaker semistable scaling (1.1) or the non-diagonality of the operator E. The paper is structured as follows.…”
mentioning
confidence: 99%